Fluoroquinolone resistance in complicated urinary tract infections: association with the increased occurrence and diversity of Escherichia coli of clonal complex 131, together with ST1193 - García-Meniño, Isidro; García, Vanesa; Lumbreras-Iglesias, Pilar; Fernández, Javier; Mora, Azucena (Frontiers in Cellular and Infection Microbiology, 2024)
Introduction Urinary tract infections (UTIs) are one of the leading causes of multidrug-resistance (MDR) spread and infection-related deaths. Escherichia coli is by far the main causative agent. We conducted a prospective study on complicated urinary tract infections (cUTIs) i) to monitor the high-risk clones that could be compromising the therapeutic management and ii) to compare the cUTI etiology with uncomplicated infections (uUTIs) occurring in the same period and health area. Methods 154 non-duplicated E. coli recovered from cUTIs in 2020 at the Hospital Universitario Central de Asturias (Spain) constituted the study collection. Results Most cUTI isolates belonged to phylogroup B2 (72.1%) and met the uropathogenic (UPEC) status (69.5%) (≥3 of chuA, fyuA, vat, and yfcV genes). MDR was exhibited by 35.7% of the isolates, similarly to data observed in the uUTI collection. A significant difference observed in cUTI was the higher level of fluoroquinolone resistance (FQR) (47.4%), where the pandemic clonal groups B2-CC131 and B2-ST1193 (CH14-64) comprised 28% of the 154 E. coli, representing 52.1% of the FQR isolates. Other prevalent FQR clones were D-ST69 (CH35-27), D-ST405 (CH37-27), and B2-ST429 (CH40-20) (three isolates each). We uncovered an increased genetic and genomic diversity of the CC131: 10 different virotypes, 8 clonotypes (CH), and 2 STs. The presence of blaCTX-M-15 was determined in 12 (7.8%) isolates (all CC131), which showed 10 different core genome (cg)STs and 2 fimH types (fimH30 and fimH602) but the same set of chromosomal mutations conferring FQR (gyrA p.S83L, gyrA p.D87N, parC p.S80I, parC p.E84V, and parE p.I529L). In addition, the plasmidome analysis revealed 10 different IncF formulae in CC131 genomes. Conclusion We proved here that non-lactose fermenting screening, together with the detection of O25b (rfbO25b), H4 (fliCH4), and H5 (fliCH5) genes, and phylogroup and clonotyping assignation, is a reasonable approach that can be easily implemented for the surveillance of emerging high-risk clones associated with FQR spread in cUTIs, such as the uncommonly reported O25b:H4-B2-ST9126-CC131 (CH1267-30). Since E. coli CC131 and ST1193 are also involved in the community uUTIs of this health area, interventions to eradicate these MDR clones, along with surveillance for other emerging ones, are essential for antibiotic use optimization programs.